Improving postsurgical paresis in brain tumor patients by transcranial magnetic stimulation - Rosenstock, Tizian; Picht, Thomas; Engelhardt, Melina; Grittner, Ulrike; Mönch, Maximilian; Vajkoczy, Peter; Lavrador, José Pedro; Mirallave-Pescador, Ana; Vergani, Francesco; Schwendner, Maximilian; Schroeder, Axel; Kram, Leonie; et al. (Journal of neuro-oncology, 2025)
Background and objectives - Recently, reduction of transcallosal inhibition by contralateral navigated repetitive transcranial magnetic stimulation (nrTMS) improved neurorehabilitation of glioma patients with new postoperative paresis. This multicentric study examines the effect of postoperative nrTMS in brain tumor patients to treat surgery-related upper extremity paresis. Methods - This is a secondary analysis of two randomized and three one-arm studies in brain tumor patients with new/progressive postoperative paresis. Patients underwent either low frequency contralesional nrTMS or sham stimulation followed by physiotherapy. Outcome was assessed on postoperative day 1, 7, and after 3 months using British Medical Research Council score (BMRC), Fugl-Meyer assessment (FMA), Karnofsky Performance Scale (KPS) and National Institutes of Health Stroke Scale (NIHSS). Results - A total of 135 patients (mean age of 53.8 years, 60 women) were included, of whom 51 patients were treated in RCTs (30 treatment group, 21 sham group) and 84 in prospective, single-arm studies. Linear mixed models showed an advantage for the treatment group for the BMRC (7 days: OR 3.28; 95%CI: 1.08–9.99; 3 months: OR 2.03, 95%CI: 0.65–6.39) and KPS (7 days: mean difference (MD) 11, 95%CI: 2–19; 3 months: MD 11, 95%CI: 2–20), less pronounced for the FMA (7 days: MD 0.28, 95%CI: -0.34-0.9; 3 months: MD 0.14, 95%CI: -0.52-0.81). A stronger treatment effect was evident with proven ischemia on the postoperative MRI. To observe an improvement by at least one grade at 3 months, the number needed to treat (NNT) for the entire cohort is 4 (BMRC) and 3 patients (KPS), respectively. Conclusion - Our multicenter data confirm the positive treatment effect of nrTMS to reduce transcallosal inhibition with a considerably low NNT - especially if caused by ischemia.
Gesehen am 29.09.2025